Influencer Popularity And Testimonials Drive Consumer Purchase Intention That Impacts Fashion Purchase Decisions - Widiastuti, Intan Sari; Syah, Muhammad Fahmi Johan (JURNAL MANAJEMEN MOTIVASI, 2025)
This study examines the impact of influencer popularity and consumer testimonials on purchase intention and its subsequent effect on fashion purchasing decisions. A quantitative method with a structural equation modeling (SEM) approach was used to analyze responses from 100 university students. The findings indicate that both influencer popularity and testimonials significantly increase purchase intention, which strongly influences purchasing decisions. However, the direct impact of influencer popularity and testimonials on purchasing decisions is not significant without the mediating effect of purchase intention. These results suggest that fostering consumer intention is critical in driving actual purchase behavior.